Comparison of Clinical and Biological/ Laboratory Findings of Malaria and Dengue Infection in Karachi. A Cross Sectional Survey - Zafar Iqbal, Shaima Sultana Memon, Jai Dev Maheshwari, Urooj Zafar, Nida Lathiya, Syed Saqib Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Malaria and dengue fever are among the most prevalent infectious diseases in tropical countries, with an approximated 219 and 50 million cases in the world, respectively. The proposed study sought to identify distinguishing clinical and biological variable of falciparum malaria and dengue. Methodology: Between September and October 2021, a cross-sectional questionnaire survey was distributed to participants in Karachi via Google form. The closed ended, self-administered questionnaire assessed symptoms of malaria, and dengue fever. Results: Of the 100 patients 67 tested positive for dengue, while 33 tested positive for falciparum malaria. Dengue positive patients had skin rash, arthralgia, retro-orbital pain, mild bleeding, thrombocytopenia and leucopenia whereas malaria positive patients had fever with chills along with splenomegaly. Other symptoms such as headache, fatigue, nausea, vomiting, myalgia, and dizziness did not differ significantly. Conclusion: In conclusion, it is possible to distinguish between dengue and malaria infections using clinical and laboratory data. These findings must be confirmed through additional study across a range of geographic locations and time periods. Keywords: Dengue, Malaria, Mild Bleeding, Retro-orbital pain, Thrombocytopenia, Leucopenia